Voxel-based analysis of age and gender effects on striatal [123I] FP-CIT binding in healthy Japanese adults - Shigemoto, Yoko; Matsuda, Hiroshi; Kimura, Yukio; Chiba, Emiko; Ohnishi, Masahiro; Nakaya, Moto; Maikusa, Norihide; Ogawa, Masayo; Mukai, Yohei; Takahashi, Yuji; Sako, Kazuya; Toyama, Hiroshi; et al. (Annals of nuclear medicine, 2022)
Objective Although previous studies have investigated age and gender effects on striatal subregional dopamine transporter (DaT) binding, these studies were mostly based on a conventional regions of interest-based analysis. Here, we investigated age and gender effects on striatal DaT binding at the voxel level, using a multicenter database of [( 123 )I] N-omega-fluoropropyl-2beta-carbomethoxy-3beta-{4-iodophenyl}nortropane ([( 123 )I] FP-CIT)-single photon emission computed tomography (SPECT) scans in 256 healthy Japanese adults. Methods We used the Southampton method to calculate the specific binding ratios (SBRs) of each subject’s striatum and then converted the [ 123 I] FP-CIT SPECT images to quantitative SBRs images. To investigate the effects of age and gender effects on striatal DaT binding, we performed a voxel-based analysis using statistical parametric mapping. Gender differences were also compared between young to middle-aged subjects and elderly subjects (age threshold: 60 years). Results When all subjects were explored as a group, DaT binding throughout the striatum decreased with advancing age. Among all subjects, the females showed higher DaT binding in the bilateral caudate compared to the males. In the young to middle-aged subjects, the females showed higher DaT binding throughout the striatum (with a slight caudate predominance) versus the males. In the elderly, there were no gender differences in striatal DaT binding. Conclusion Our findings of striatal subregional age- and gender-related differences may provide useful information to construct a more detailed DaT database in healthy Japanese subjects.